3D printing geopolymer nanocomposites: Graphene oxide size effects on a reactive matrix. (30th August 2020) - Zhou, Guo-Xiang; Li, Cheng; Zhao, Zhe; Qi, Yu-Zhao; Yang, Zhi-Hua; Jia, De-Chang; Zhong, Jing; Zhou, Yu
Abstract: In previous study, we reported that the addition of graphene oxide (GO) into geopolymer can significantly modified its rheology properties and make it 3D printable. However, the high concentration of GO employment limits the enhancement of mechanical properties. Improving GO reinforcement efficiency with lower GO concentration without sacrificing 3D printability is still a challenge. More importantly, although it has been proved that large graphene oxide (LGO) can reinforce various matrix materials including polymers and ceramics better than that of small graphene oxide (SGO), it is still unclear whether such conclusion can be directly applied to reactive matrix system. We investigate the effects of GO size on mechanical properties of geopolymer with low GO concentration, both at material level and printed structure level. Surprisingly, it is found that the SGO can enhance the mechanical performance of geopolymer more effectively than LGO at material level, which is resulted from the fact that the chemical reaction between geopolymer particles could be severally blocked by LGO. In addition, we also found that the efficiency for the reinforcement at structure level is higher for LGO. Therefore, the size of nano reinforcement should be optimized both for the reinforcement at material and structure level. Graphical abstract: Image 1